Can you speak English at school? Yes, we can!: análise e propostas para a produção oral em língua inglesa na coleção It fits do PNLD-2014 - Dias, Vanessa Logue (Universidade do Vale do Rio dos Sinos, 2015)
This study follows the principles of sociocultural theory (VYGOTSKY, 1984; LANTOLF, 2000; SWAIN, 2006) to discuss the foreign language teaching-learning process. It aims to analyze oral production activities belonging to the didactic series It Fits, from PNLD-2014 (Brazilian National Program of Textbooks - 2014). According to the PNLD-2014 Guide (BRASIL, 2013), It Fits was the only foreign language didactic collection to receive the maximum score for the speaking activities, an ability which is usually not emphasized in the textbooks distributed to Brazilian public schools. Thereby, we observed how the oral production is proposed in the textbooks of the didactic collection, trying to identify the positive aspects and points to be improved in the proposed activities. In order to carry out the analysis, some criteria were developed to verify whether the oral production activities stimulate the three kinds of knowledge in focus: systemic, world and textual (BRASIL, 1998), literacy (BIONDO, 2012), collaboration (DONATO, 1994) and genres construction (DIAS, 2009). The results revealed that the textbook collection brings good speaking activities, mostly serving well the analysis criteria. However, the oral production proposed in the didactic series needs more collaborative occasions in the genre construction process. Considering collaboration as an essential element in the process of learning a foreign language, this study makes some suggestions for adaptations of some activities in order to turn them into tasks: pedagogical situations in which students work collaboratively to achieve common learning goals. (SWAIN; LAPKIN, 2001). Therefore, the teacher who uses the material can use these suggestions in order to expand the significant oral production opportunities in the English language classroom.
Keywords: Língua inglesa; Colaboração; Livros didáticos; Produção oral; English; Collaboration; Textbooks; Oral production; ACCNPQ::Lingüística, Letras e Artes::Lingüística